Telaah Normatif Pelaksanaan Prinsip Transparan, Partisipatif, Objektif, Akuntabel, Dan Terbuka Dalam Pemilihan Hakim Mahkamah Konstitusi Untuk Mewujudkan Pasal 15 Ayat (1) Undang-Undang Nomor 7 Tahun 2020 Tentang Perubahan Ketiga Atas Undang-Undang Nomor 24 Tahun 2003 Tentang Mahkamah Konstitusi - Djufri, Darmadi; Kesuma, Derry Angling (Consensus : Jurnal Ilmu Hukum, 2026)
The trifurcation of the selection mechanism for constitutional judges cannot be separated from the construction of norms in the Constitutional Court Law, which regulates the selection of constitutional judges with a high degree of flexibility so that it can be interpreted freely and according to the preferences of each regime by institutions that have the constitutional authority to nominate constitutional judges. If left unchecked, this will lead to chaotic conditions in the recruitment of constitutional judges, which will ultimately produce constitutional judges with low qualifications. Transparency in the recruitment of judge candidates from the early stages can increase the contribution of the public in providing input regarding the track record of constitutional judge candidates. Public participation in the recruitment system for constitutional judge candidates is necessary in order to produce ideal constitutional judges. There is controversy among experts in administrative law, but the dynamics of statehood require dissenting opinions in order to find someone who meets the expectations of many people. The selection of Adis Kadir as a judicial candidate by the House of Representatives (DPR) will always have the potential to trigger public debate.